Factores sociodemograficos-laborales y la satisfacción laboral de la enfermera Hospital Belén de Trujillo - Alcalde Caballero, Rosa Elena (2019)
This descriptive correlation research aims to determine the relationship between Sociodemographic-Labor Factors and the Labor Satisfaction of emergency services nurses at the Hospital de Belén in Trujillo in a population of sample of 35 nurses who gave two instruments relating to sociodemographic factors and job satisfaction, the Fisher test was used statistically to reach the following conclusions: higher percentage achieved in variables; In terms of age it was 34.3% for the ranges of 25 to 35 years and 36 to 45 years. In addition, 100.0% of nurses are women, 68.6% were in marital status, 71.4% of nurses are named. As for the years of professional practice 40.0% from 5 to 15 years, in terms of training studies 45.7% specialist with completed studies /title, and 28.6% have a master's degree, concluding that 60.0% have an average level of job satisfaction and are related with the variables of age, employment situation, years of professional practice, postgraduate training and postgraduate master's degree, where all relationships had a p-value (Fisher) of less than 0.05, and there is no relation to the variable marital status.